Novel 1-Glycyl-3-Methyl Imidazolium Chloride-Iron(III) Complex for Synthesis of Propargylamines - Karthikeyan, Parasuraman; Sachin Arunrao, Aswar; Prashant Narayan, Muskawar; Senthil Kumar, S.; Suresh Kumar, Sythana; Rambhu Bhagat, Pundlik (Asian Journal of Chemistry, 2012)
The development of a highly efficient, 1-glycyl-3-methyl imidazolium chloride-iron(III) [Gmim-Fe(III)] complex, catalyst for the three-component coupling reaction of aldehydes, alkyne and amine (A3-coupling) was described. In the presence of [Gmim-Fe(III)] (0.05 mmol), the A3-coupling reaction were carried out at room temperature under solvent-free reaction condition and the corresponding propargylamines were generated in good to excellent yields. Both aliphatic and aromatic aldehydes were used in the reaction. Furthermore, the catalyst could be reused several times without a significant loss of its catalytic activity.